PENERAPAN METODE DSS (MAUT & IRR) DALAM MENENTUKAN KELAYAKAN PENGADUAN - Andi Nurfadillah Ali; Khaera Tunnisa (SINTECH (Science and Information Technology) Journal, 2022)
The research and development center for mineral and coal technology or abbreviated as Puslitbang tekMIRA is located in Bandung, West Java, which has asset management, namely the rental of rooms or buildings. In asset management, there is a complaint page if a customer has a complaint. Based on the complaint data that came in at the same time, the authors saw that there were problems that were considered to need attention, namely which complaints would be resolved first and whether or not the complaint was feasible or not to be processed. This study uses the DSS (Decision Support System) method, namely Multi Attribute Utility Theory (MAUT) and IRR (Internal Rate of Return). The MAUT method is a method that converts some importance into a numerical value from a scale of 0-1 which represents the worst and best values ​​and the final result is a ranking. While the IRR method is an indicator of the efficiency level of an investment that is used to provide an overview of whether the complaint is feasible or not to be followed up. The result of the application of this method is the feasibility of the complaint.